Trends in the Media Industry of South America in the digital transition - Campos-Freire, Francisco (2017)
Traditional media (press, radio and television) in South America have better expectations regarding the process of digital transition faced by communication companies and industries on a global level. This hypothesis is contrasted by comparing two elements. First, the evolution trends of the media sector in Latin America collected by sectorial databases of the World Association of Newspapers and New Publishers, the Eurodata´s general audience report, the Pew State of the News Media and the Global Entertainment & Media Outlook 2016-2020. Second, the results of an own survey to 166 managers from 19 Latin American countries. Media managers from the area confirm that traditional media will grow up to 5% and digital media and advertising could reach 10% and more in the coming years..